Therapeutic Response of Wilsons disease to D-Penicillamine in Paediatric Population: A one year follow-up study - Saha, NC; Sultana, A; Mollah, MAH; Begum, T; Rahman, AKMM; Fatmi, LE (Journal of Dhaka Medical College, 2010)
Objectives: The objective of this study was to observe the outcome of patients treated with penicillamine. Design: Intervention type of study Setting: Department of Paediatrics, Dhaka Medical College Hospital Study period: January 2007 to December 2008. Study subjects: Sixteen diagnosed cases of Wilson's disease as per inclusion criteria. Intervention: D-penicillamine was started in a low dose, which was titrated gradually. The clinical and biochemical parameters were evaluated to look for the response to treatment. Results: A total of 16 cases were included. Among them 12 were male and 4 were female. The mean (± SD) of age of the patients was 10 (± 2.34) years. Consanguinity between parents was present in 44% (n=7). The hepatic and neurological variety of WD were 56 % (n=9) and 44% (n=7) respectively. The K-F ring was present in 75% (n=12/16) of WD cases. The excretion of 24 hrs urinary copper was steadily increased from discharge till second follow-up in response with increasing dose of penicillamine, thereafter the value was declining gradually till final follow-up at 1 year. Regarding outcome, 7 patients improved of which 4 were in hepatic and 3 in neurological group, 3 of hepatic WD expired and 2 developed neurological manifestations. One patients developed proteinuria while penicillamine treatment .About half of patients with WD were improved. Adequate cupriuresis occurred at three months. All the symptoms and biochemical markers WD improved gradually. No significant side effect was seen. Key words: Wilson's disease; penicillamine; urinary copper. DOI: 10.3329/jdmc.v18i1.6304 J Dhaka Med Coll. 2009; 18(1) : 37-43